Potential of the dense media cyclone for gold ore preconcentration. Issue 1 (2nd January 2020) - Mkandawire, N. P.; McGrath, T.; Bax, A.; Eksteen, J.
ABSTRACT: The dense media cyclone (DMC) has had wide application in beneficiation of coal, iron ore, diamonds and base metals, with limited applications in preconcentrating precious metals such as gold. This paper reports and discusses data from experimental evaluations of the DMC for preconcentrating gold ores. Two ore types were tested in the particle size range from 0.3 mm to 4.75 mm which was considered a pumpable size range. A DMC with a diameter of 100 mm was used to separate the gold ores at separation densities ranging from 2.55 g/cm³ to 2.95 g/cm³. Evaluation of the data confirms the potential of the DMC for gold ore preconcentration, with some ores being more amenable to gangue rejection than others. An optimum density of separation is required for a given type of ore in order to achieve balance between overall mass rejected and gold recovery.